The Influence of the Jigsaw Model Based on Higher Order Thinking Skills on Students 21st Century Skills : Meta-Analysis - Everhard Markiano Solissa; Kartini Marzuki; Arniati Arniati; Dhini Mufti; Tomi Apra Santosa (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of the study was to determine the effect of jigsaw learning model based on Higher Order Thinking Skills on students' 21st century thinking skills. This type of research is quantitative research with a meta-analysis approach. The data sources in this study came from 10 national and international journals published in 2018-2023. The process of searching for data sources through google scholar, Eric and Wiley databases. The inclusion criteria in this study are a) research must have experimental and control classes, b) research comes from Scopus and SINTA indexed journals or proceedings, c) research has a relationship with the Higher Order Thinking Skills-based jigsaw learning model towards students' 21st century skills, d) research must be published in the last 5 years range 2018-2023; e) articles must have a value (t), (r), (f); f) sample size> 20 students. Data analysis in this meta-analysis with the help of JSAP 0.8.5 application. From this meta-analysis, it can be concluded that there is a significant effect of jigsaw learning model based on Higher Order Thinking Skills on students' 21st century thinking skills (Z = 1.431; p < 0.001; 95% CI [0.612; 0.942]. This effect is criterion high (rRE = 0.845). This finding explains the learning model of jigsaw learning model based on Higher Order Thinking Skills provides a high influence on students' 21st century thinking skills.